(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Euphemism and dysphemism are widely seen as opposite aspects of one linguistic phenomenon. However, there are facts of their use that raise questions about their status in relation to each other. This paper investigates functional side of dysphemism to define if it is opposite to euphemism. This research shows that functions that dysphemisms perform in text are similar to those fulfilled by euphemisms. However, there are details of their use such as their frequency, purpose, and intentions of the speaker that demonstrate that their opposition to each other is not absolute.